PERANCANGAN KOMIK PERUBAHAN SOSIAL BUDAYA MINANGKABAU - Drs. Abd. Hafiz, M.Pd., Syahrul Azmi, Drs. Mediagus, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2018)
The purpose of the creation of this work is: Visualize the socio-cultural changes of Minangkabau society in the form of comics. Cultivated by applying the principles of art, such as unity, rhythm, balance and contrast. The coloration of this comic combines secondary and primary colors and in the preparation of drawings and sentences adjusting to the principle of layout and typography, with initial cultivation using a pencil and ending with the help of computer applications to present the work in the form of comic books. The process of cultivating this work using several stages, namely: preparation, elaboration, synthesis, concept realization, and finishing (finishing). The work tha Â the author has written entitled